Innovation and Sustainability - GÜNERİ, Mukadder (European Journal of Multidisciplinary Studies, 2017)
When we look at the history of humanity, it is seen that mankind has been experiencing a process of change that has not lived to this day. This process we are in is called globalization. There are many opinions about the happiness and the unhappiness of mankind related to globalization. Globalization is on the verge of questioning what sustainability will bring when it is thought of in the long run. On this result, when we search for answers to questions about what you can sustain; when we look for answers to this question, what is sustainability? Innovation comes to the forefront, which is two dimensions, technical and organizational. Whether the individual the private or the public the conditions of innovation are reflected in education and training. In the process we are in today (the developments in economic, cultural and socio-economic relations between countries), it is evident that it is imperative to have education and training to respond to the sustainability of innovation conditions. All these principles make life, life style. That is, to acquire information, to produce information, to produce common values, to protect social and individual values in the common values produced, to adapt to the rapid development of technology, to increase quality of life in existing conditions, to produce added value in existing conditions and to maintain its sustainability. In this work, the relevance of innovation to sustainability has been examined in a classical way.